Synthesis some new 8-aza-2,3-dioxabicyclo[4.3.0]nonane derivatives by manganese(III)-catalyzed reaction - My Trinh, Le Thi; Ha, Nguyen Van (Vietnam Journal of Chemistry, 2015)
Some new 8-aza-2,3-dioxabicyclo[4.3.0]nonane derivatives bearing different substituents at the 4-position were synthesized in high yields.  This was done by using the reaction of 1,1-disubstituted ethenes with methyl 1-benzyl-2,3-pyrrolidinedione-4-carboxylate in the presence of manganese triacetate dihydrate as a catalyst.  The spectrometric features and the reaction mechanism are discussed. Keywords. Oxygen molecule trapping reaction, 8-aza-2,3-dioxabicyclo[4.3.0]nonanes, manganese(III) catalyst